The Legal Impacts of The Convention for The Conservation of Southern Bluefin Tuna on The Optimum Utilization and Sustainability of Highly Migratory Fish - Sri Wartini (Faculty of Law, Universitas Jenderal Soedirman, 2019)
The sustainability of southern Bluefin tuna (SBT) is very important, since the SBT as one of the highly migratory fish which is very valuable. Because of that, the SBT are exploited tremendously and it caused serious decline of the population. Due to the reasons, the aim of the paper is to examine comprehensively the legal impacts of the Convention for The Conservation of Southern Bluefin Tuna (CCSBT) on the optimum utilization and sustainability of the SBT as one of highly migratory fish, There are two problems questions that are proposed, namely, first, how is the role of the Commission of CCSBT in the optimum utilization and sustainable conservation of the SBT. Second, how is the legal impacts of the CCSBT to the conduct of the Member States to obey the obligations of the CCSBT in order to utilize and to maintain the sustainability of the SBT in sustainable manner. The result of the paper finds that there is positive legal impacts of the CCSBT to the Member States’ conduct in order to materialize the optimum utilization and sustainability of the SBT, though, there are still some challenges. Keywords: conservation, highly migratory fish, optimum utilization, southern tuna Bluefin, sustainable manner.Southern Bluefin Tuna (SBT), as one of the highly migratory fish, is very valuable due to the high demand inthe international market. Hence, the SBT is exploited tremendously and it caused a severe decline in thepopulation. To maintain the sustainability utilization of SBT, the role of the Commission on the CCSBT isimperative. The objective of the research is to examine conceptually the legal impacts of the Convention forthe Conservation of Southern Bluefin Tuna (CCSBT) on the optimum utilization and sustainability of the SBT.It is a normative juridical research by applying conceptual and statutory approaches. The results of theresearch indicates that: first, the role of the Commission of CCSBT in the optimum utilization and thesustainability of the SBT is very significant: second, there are positive legal impacts of the CCSBT to theconduct of the Member States to comply with provisions of the CCSBT; third, the legal impacts of CCSBT areable to oblige the Member States to perform their obligations, however, there are still some challenges tomaterialize the objective of the CCSBT.Keywords: conservation; highly migratory fish; optimum utilization; southern tuna bluefin; sustainability.